Deficiency of the ferrous iron transporter FeoAB is linked with metronidazole resistance in Bacteroides fragilis - Veeranagouda, Yaligara (Oxford University Press, 2014)
BACKGROUND: Metronidazole is the most commonly used antimicrobial for Bacteroides fragilis infections and is recommended for prophylaxis of colorectal surgery. Metronidazole resistance is increasing and the mechanisms of resistance are not clear. METHODS: A transposon mutant library was generated in B. fragilis 638R (BF638R) to identify the genetic loci associated with resistance to metronidazole. RESULTS: Thirty-two independently isolated metronidazole-resistant mutants had a transposon insertion in BF638R_1421 that encodes the ferrous transport fusion protein (feoAB). Deletion of feoAB resulted in a 10-fold increased MIC of metronidazole for the strain. The metronidazole MIC for the feoAB mutant was similar to that for the parent strain when grown on media supplemented with excess iron, suggesting that the increase seen in the MIC of metronidazole was due to reduced cellular iron transport in the feoAB mutant. The furA gene repressed feoAB transcription in an iron-dependent manner and disruption of furA resulted in constitutive transcription of feoAB, regardless of whether or not iron was present. However, disruption of feoAB also diminished the capacity of BF638R to grow in a mouse intraperitoneal abscess model, suggesting that inorganic ferrous iron assimilation is essential for B. fragilis survival in vivo. CONCLUSIONS: Selection for feoAB mutations as a result of metronidazole treatment will disable the pathogenic potential of B. fragilis and could contribute to the clinical efficacy of metronidazole. While mutations in feoAB are probably not a direct cause of clinical resistance, this study provides a key insight into intracellular metronidazole activity and the link with intracellular iron homeostasis.